Profil Partisipasi Mahasiswa Universitas Jambi pada Program Merdeka Belajar Kampus Merdeka (MBKM) Periode 2021-2023 - Hidayati, Hidayati; Winarni, Sri; Wicaksana, Ervan Johan; Ardianingsih, Ardianingsih; Sunarti, Sunarti (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to present and describe the level of student participation from each faculty as well as data related to the level of student participation in each form of Merdeka Belajar Kampus Merdeka (MBKM) activity. In addition, this research aims to explain the inhibiting factors in each form of Merdeka Belajar Campus Merdeka (MBKM) activity in each faculty. Research data related to the number of students participating in the Merdeka Belajar Kampus Merdeka (MBKM) activity was obtained from the Independent Campus Learning Academic System (SIAKADEKA) application. The research results found that (1) in general the participation level of Jambi University students has increased from year to year; (2) the number of Independent Learning Campus (MBKM) participants for each form of learning activity experiences fluctuating trends and increasing trends; and (3) each faculty has different characteristics of forms of learning activities (BKP) which are characterized by the number of participants who dominate in certain forms of learning activities (BKP).